Fides Quaerens Intellectum: Rasionalitas Iman sebagai Bentuk Apologia dalam Kajian 1 Petrus 3:15 (Pusat Riset dan Inovasi Nasional, 2026)
The concept of fides quaerens intellectum (faith seeking understanding) in this study is interpreted by emphasizing the rationality of faith as a form of apologia based on 1 Peter 3:15. This study aims to demonstrate that Christian faith is not merely spiritual and normative in nature, but also possesses a rational dimension that can be intellectually justified. In this context, 1 Peter 3:15 serves as a biblical foundation that underscores the importance of believers being prepared to provide a logical and responsible explanation for the hope they possess.This research employs a qualitative approach through library research, combined with an exegetical analysis of 1 Peter 3:15 and a philosophical-theological approach to understand the relationship between faith and reason. Through this framework, the rationality of faith is examined as an integral part of the Christian apologetic tradition. Furthermore, this study affirms that faith and reason are not contradictory realities, but rather complementary elements in the pursuit of truth. The findings indicate that the rationality of faith functions not only defensively but also constructively in fostering dialogue between faith and the intellectual world. Christian faith is understood as a conviction that remains open to rational examination without losing its dimension of mystery. Therefore, fides quaerens intellectum emerges as a relevant paradigm in addressing modern challenges, while also contributing to the development of theological and philosophical studies, particularly in strengthening the integration of faith and reason in the life of believers.